Investigation of the influence γ-irradiation on the mechanical properties of the polyimide composite material system «Polyimide – YBa2Cu3O6+x » - Мұрaдов А.Д.; Сыдықовa A.A.; Суюндыковa Г.С. (Recent Contributions to Physics, 2016)
It is found that the filler YBa2Cu3O6+x influences the morphology of the polymer surface roughness topography mainly clustered morphology suitable formulations. The effect of different doses of 150 kGy, 250 kGy and 600 kGy of γ- irradiation on the mechanical properties of the «Polyimide – YBa2Cu3O6+x » system. Comparing the Raman spectra of the composite material YBa2Cu3O6 + x with that of pure polyimide. A change of two peaks of the polymer filled with 0.01 wt% and 0.05 wt%. At a concentration of 0.1% by weight of all the highs is decreased.